Taking context seriously: explaining widening access policy enactments in UK medical schools. Issue 1 (January 2015) - Cleland, Jennifer A; Nicholson, Sandra; Kelly, Narcie; Moffat, Mandy
<x xml:space="preserve">Abstract</x> Context Since the 1970s, the UK medical student body has become increasingly diverse in terms of gender, ethnicity and age, but not in socio‐economic background. This variance may be linked to large differences in how individual medical schools interpret and put into practice widening participation (WP) policy. However, attempts to theorise what happens when policy enters practice are neglected in medical education. We aimed to explore the dynamics of policy enactment to give a novel perspective on WP practices across UK medical schools. Methods We used a qualitative design employing individual telephone interviews to elicit views and concerns around WP from admissions deans and admissions staff within UK medical schools. We carried out interviews with representatives from 24 of 32 UK medical schools. Data coding and analysis were initially inductive, using framework analysis. After the themes emerged, we applied a deductive framework to group themes into four contextual dimensions of 'situation', 'professional', 'material' and 'external'. Results Our participants held different positions in relation to the interpreting and translating of WP policy, which were influenced by a number of contextual factors including: geographical locality and positioning of the medical school; the expectations of the university and other key stakeholders, and resources. The latter were subtle and referred to resources for medical selection processes rather than for WP per se. The data hinted that the political goal of WP and medical education's goal of producing the best doctors may conflict. Conclusions This is the first study to explicitly explore WP policy enactment in medical education. Our analysis is useful for understanding differences in how WP policy is played out in local contexts, and for planning for future policy enactment and research. The messages identified will resonate internationally with all those engaged in efforts to widen participation in medical education.